BLAZE YOUR OWN TRAIL;AN INTERACTIVE GUIDE TO NAVIGATING LIFE WITH CONFIDENCE, SOLIDARITY, AND COMPASSION - REBEKAH BASTIAN (BERRETT-KOEHLER, 2020)
A modern, feminist take on the classic choose-your-own-journey book, inspiring readers to embrace the fact that there is no singular right path--just your own! So many women enter their adult lives believing that they should know where they are going and how to get there. This can make life decisions feel intimidating and overwhelming. While some choices that lie ahead are fairly predictable, such as those surrounding career, partnership, and motherhood, the effects of these choices can lead to more complicated and unexpected turns that are seldom discussed. Rather than suggesting a rule book, Rebekah Bastian, vice president at Zillow and recognized thought leader, inspires you to Blaze Your Own Trail. "I have the benefit of being a living example of crooked paths, magnificent screw-ups, and shocking successes, "she writes. Through storylines and supportive data that explore workplace sexism, career changes, marriage, child-rearing, existential crises, and everything in between, you will learn to embrace and feel less alone in your own nonlinear journey. Even better, you can turn back decisions and make different ones. Blaze Your Own Trail includes nineteen possible outcomes and many routes to get there. You will find that you have the strength to make it through any of them.